Fracture assessment of flawed girth weld in clad pipelines with mismatch weld strengths - Kee, E Peng (2016)
Offshore pipelines are constantly subjected to large plastic deformations due to different displacement controlled loading conditions; however, current engineering critical assessment (ECA) protocols adopted by industries such as BS 7910:2013 are developed from load controlled loading condition. Concerns regarding the structural integrity of pipelines are raised as potential defects in weldments increase the likelihood of fracture leading to complete failure of pipelines. This study pursues understanding of crack tip opening displacement (CTOD) evolution for weldments with mismatched mechanical properties, as well as to appraise the suitability of stress-based fracture assessment approach. Therefore, 3D elastic-plastic finite element simulations are conducted for different mismatch conditions. The defect investigated is a canoe shape surface crack located at middle of girth weld, where the pipeline segments are simulated under pure bending until maximum global strain of 3%. Influences of different crack parameters on CTOD such as crack depth and crack length to perimeter diameter ratio, as well as geometrical configurations of weldment are examined herein. The simulations indicate that crack length is not of paramount importance for shallow crack. It also illustrates the rate of increment for CTOD exhausted over larger crack length. Similar observations are found in different mismatch conditions and hence the conclusion is consistent. Furthermore, the results demonstrate that throughout different mismatch conditions, average widths of weldment and effective crack depth of weldment are the key parameters for weldments that have different geometrical configurations. Subsequently, a strain-based failure assessment diagram (FAD) is constructed using FE simulations results. Fracture assessment results computed from BS 7910:2013 are used to compare with strain-based FAD. The comparison lends strong support to adopt strain-based fracture assessment procedures, as the former produces over-conservative predictions.